Incidencia del síndrome de burnout en el desempeño laboral de los técnicos y conductores del proyecto de innovación tecnológica participativa y productividad agrícola del ministerio de agricultura ganadería, acuacultura y pesca, planta central Quito en el período 2017. - Cabrera Armijos, Richard Andres (2017)
The main objective of the research project was to determine the incidence levels of Burnout Syndrome in the performance of the Personnel of the Participatory Technological Innovation and Agricultural Productivity Project of the city of Quito, Central Plant. The investigation was carried out in the city of Quito in the period December 2016 - March 2017. The personnel that formed part of the investigation was the entire payroll of the organization with a total of 40 members. The information obtained was collected through 3 questionnaires: ISTAS 21, MBI-GS and Labor Performance Survey to determine the existence of Burnout Syndrome and its influence on performance. The results obtained were tabulated and explained in this process. Through the investigate the presence of emotional exhaustion could be verified: feelings of frustration, apathy and depression, and work overload as causes of the Burnout Syndrome being this in turn the reason for the poor performance of the Work, applying the Maslach method was verified that the professionals have an average level of Burnout, backed by the statistical analysis applied to the t - Student method shows that there is a relationship between performance and burnout syndrome, obtained through the instruments applied to employees of the company. The measure of prevention and reduction of the mentioned problem was developed of a Guide to Prevention of the Syndrome of Burnout.